Histomorphometric Analysis of Pulp-Dentin Complex in Relation to Tooth Development and Eruption Patterns - Safdar, Shamayem; Iqbal, Sarosh; Irfan, Fahmoona; Mujeeb, Rida; Ali, Noman; Zahra, Rubbab (Journal of Neonatal Surgery, 2025)
Background: The pulp-dentin complex is a dynamic structure that is important in the development, nutrition, and defense of teeth. Objective: To examine the histomorphometric characteristics of the pulp-dentin complex, as well as to test the hypothesis of their connection to the tooth development and eruption times. Methods: The study was an observational cross-sectional study of 80 extracted permanent human teeth that were gathered within one year at Faryal Dental College, Shaikhpura. Teeth that were at different developmental and eruption stages were histologically analyzed after being processed, decalcified, sectioned, and stained using the hematoxylin and eosin stain. The data were processed in SPSS v25; the group comparisons were done with ANOVA, and Pearson correlation was used to evaluate the developmental stage relationships. A p-value that was below 0.05 was notable. Results: The pulp chamber area was smaller in unerupted (12.5 ± 0.1 mm2) and fully erupted teeth, whereas the dentin thickness, predentin width, and odontoblast densitywere significantly greater in fully erupted teeth. The developmental stage had a negative correlation with the pulp chamber area (r = −0.82), whereas dentin thickness, predentin width, and odontoblast density had positive relationships (p < 0.05). Conclusion: Pulp-dentin complex is predicted to experience a systematic structural alteration throughout the development and eruption of the teeth. Such histomorphometric observations can be used in clinical dentistry, age determination, and forensics by offering normative information about pulp and dentin structure.. .